The effects of morus nigra on the alveolar bone loss in experimentally-induced periodontitis - Yildirim, Tuba Talo; Ozan, Gonca; Dundar, Serkan; Bozoglan, Alihan; Karaman, Tahir; Dildes, Neval; Erdem, Elif (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Purpose The aim of this study is to evalute the anti-inflammatory effects of morus migra on experimentally-induced periodontitis in rats. Materials and Methods Twenty-four Wistar-albino rats were randomly divided into three groups: control group (C, n=8), experimental periodontitis (PER, n=8), experimental periodontitis and treated with Morus nigra (MN+PER, n=8) (50 mg/kg per day for 21 days). After 21 days, the rats were sacrificed, and alveolar bones were evaluated histopathologically and histometrically analyzed to obtain level of alveolar bone loss. The detection of RANKL and OPG were immunohistochemically performed. Serum and tissue levels of MMP-8 and MMP-13 were also analyzed. Results Morus nigra treatment decreased tissue MMP-8 and MMP-13 levels and there were significant differences in the case of tissue levels of MMP-8 and MMP-13 between groups PER and MN+PER (p=0.035, p=0.041). There were no significant differences among all the groups serum levels of MMP-8 and MMP-13 (p=0.067, p=0.082). In the histometric evaluation, alveolar bone loss was greater in the PER group compared to C and MN groups (p=0.035). Immuno-histochemical staining of RANKL activities were found significantly lower (p=0.037) and OPG activities were found significantly higher in MN+PER group when compared to PER group (p=0.021). Conclusion The present study reveals that systemic administration of Morus nigra significantly inhibited the regional alveolar bone resorption and contributes to periodontal healing in the rat experimental-periodontitis models.
Keywords: Experimental periodontitis; cytokines; MMP-8; MMP-13; morus nigra